A mediação do processo de aprendizagem em crianças com baixa visão: brincadeiras utilizadas pelo professor na educação infantil - SOARES, Dlayne Giordana Pereira (2019)
Playing is a fundamental experience for any age, especially for children in early childhood education. It is by playing, playing, that the child reveals his cognitive, visual, auditory, tactile, motor state, his way of learning and developing a cognitive relationship with the world, people, things and symbols. Thus, play should no longer be an activity used by the teacher just to recreate, but should be developed using strategies that encourage learning. In this work, it was analyzed how the teacher uses play to mediate the learning process of children with low vision in early childhood education in public schools in São Luis/MA. To this end, a qualitative, exploratory-descriptive research was carried out, based on the descriptive analysis of the action, with a case study. Three teachers from an early childhood school in the municipality participated in this experience report, and they work with children who have low vision. For data collection, observation and semi-structured interviews were used and for the analysis of results, methodologies based on data analysis were used. The results were relevant to the research since, it was noticed that the teachers interviewed gave their contributions to the research and then mediated the teaching and learning process of the child with low vision.